Characterization of a recombinant matrix metalloproteinase-2 from sea cucumber (Stichopus japonicas) and its application to prepare bioactive collagen hydrolysate. (September 2018) - Yan, Long-Jie; Jin, Tengchuan; Chen, Yu-Lei; Zhan, Chun-Lan; Zhang, Ling-Jing; Weng, Ling; Liu, Guang-Ming; Cao, Min-Jie
Graphical abstract: Highlights: MMP-2 gene was first cloned from sea cucumber ( Stichopus japonicas ). The expressed MMP-2 showed gelatinolytic activity after refolding. rMMP-2 exhibited optimal activity at pH 8.5 and 40 °C. rMMP-2 efficiently degraded collagen and the hydrolysate revealed antioxidant activity. Abstract: Matrix metalloproteinase(s) (MMPs) are involved in collagen metabolism in sea cucumber. In the present study, a complete coding region of MMP-2 gene was cloned from the body wall of sea cucumber ( Stichopus japonicas ) and the open reading frame contained 1887 bp encoding 629 amino acid residues. The deduced amino acid sequence of MMP-2 contained a signal peptide, a propeptide domain, a catalytic domain with three repeats of fibronectin-type II region and a C-terminal hemopexin-like domain. According to the domain prediction of MMP-2, its catalytic domain was successfully expressed in Escherichia coli . After refolding, the purified recombinant MMP-2 (rMMP-2) exhibited a single band both on SDS-PAGE and zymography gel. The molecular mass of rMMP-2 was approximately 40 kDa. Circular dichroism spectrum revealed that the denaturation temperature of rMMP-2 was 56.80 ± 0.25 °C. Enzymatic characterization of rMMP-2 showed that it hydrolyzed gelatin most effectively at pH 8.5 and 40 °C, suggesting it is a slight alkaline proteinase. In addition, Ca 2+ was required for optimal gelatinolytic activity. The rMMP-2 degraded collagen effectively and the hydrolysate revealed scavenging activities on both 2, 2'-diphenyl-1-picrylhydrazyl free radical and hydrogen peroxide. These results indicated that rMMP-2 could potentially be applied for preparation of bioactive collagen hydrolysate.